Knowledge of Sexually Transmitted Infections with Focus on HIV/AIDS and Hepatitis B among Secondary School Adolescents in Ekiti State, Nigeria - Oluremi Olayinka Solomon; Olusoji Abidemi Solomon,; Eyitope Oluseyi Amu; Victor Mayowa Adeleye; Paul Oladapo Ajayi; Mojoyinoluwa Oyindamola Adeoson (Global Journal of Medicine and Public Health)
Sexually transmitted infections (STI) are a serious public health issue among adolescents because they often have